PD‐L1 blockade enhances response of pancreatic ductal adenocarcinoma to radiotherapy. Issue 2 (8th December 2016) - Azad, Abul; Yin Lim, Su; D'Costa, Zenobia; Jones, Keaton; Diana, Angela; Sansom, Owen J; Kruger, Philipp; Liu, Stanley; McKenna, W Gillies; Dushek, Omer; Muschel, Ruth J; Fokas, Emmanouil
Abstract: Pancreatic ductal adenocarcinoma (PDAC) is considered a non‐immunogenic tumor, and immune checkpoint inhibitor monotherapy lacks efficacy in this disease. Radiotherapy (RT) can stimulate the immune system. Here, we show that treatment of KPC and Pan02 murine PDAC cells with RT and gemcitabine upregulated PD‐L1 expression in a JAK/Stat1‐dependent manner. In vitro, PD‐L1 inhibition did not alter radio‐ and chemosensitivity. In vivo, addition of anti‐PD‐L1 to high (12, 5 × 3, 20 Gy) but not low (6, 5 × 2 Gy) RT doses significantly improved tumor response in KPC and Pan02 allografts. Radiosensitization after PD‐L1 blockade was associated with reduced CD11b + Gr1 + myeloid cell infiltration and enhanced CD45 + CD8 + T‐cell infiltration with concomitant upregulation of T‐cell activation markers including CD69, CD44, and FasL, and increased CD8:Treg ratio. Depletion of CD8 + T cells abrogated radiosensitization by anti‐PD‐L1. Blockade of PD‐L1 further augmented the effect of high RT doses (12 Gy) in preventing development of liver metastases. Exploring multiple mathematical models reveals a mechanism able to explain the observed synergy between RT and anti‐PD‐L1 therapy. Our findings provide a rationale for testing the use of immune checkpoint inhibitors with RT in PDAC. Synopsis: Local recurrence is a major cause of morbidity and mortality in pancreatic ductal adenocarcinoma (PDAC). Here, radiotherapy (RT) and gemcitabine chemotherapy are shown to have substantial immunomodulatory effects, including upregulation of PD‐L1. RT and gemcitabine chemotherapy induce PD‐L1 upregulation mediated by Jak/Stat1 signaling in PDAC cells. PD‐L1 blockade enhances primary tumor response to high‐dose RT and chemoradiotherapy and decreases formation of liver metastases in PDAC. Combination of RT and PD‐L1 blockade promotes infiltration and activation of cytotoxic T cells but decreases myeloid and Treg cell numbers. Mathematical modelling can provide an explanation of the complementary role of RT with PD‐L1 inhibition in PDAC. Abstract : Local recurrence is a major cause of morbidity and mortality in pancreatic ductal adenocarcinoma (PDAC). Here, radiotherapy (RT) and gemcitabine chemotherapy are shown to have substantial immunomodulatory effects, including upregulation of PD‐L1.